Evaluating Program Impacts on Mature Self-help Groups in India - Deininger, Klaus; Liu, Yanyan (Oxford University Press on behalf of the World Bank, 2014)
Despite the popularity and the unique nature of women's self-help groups in India, evidence on the economic impact of these groups is scant. On the basis of two rounds of surveys of 2,517 households, we use a strategy of double differences and propensity score matching to assess the economic effects of a program that promoted and strengthened self-help groups in Andhra Pradesh in India. Our analysis finds that longer exposure to the program has a positive impact on consumption, nutritional intake, and asset accumulation. Our investigation into the heterogeneity of these effects suggests that even the poorest households are able to benefit from the program.